Decision Support System for Strategic Planning in Educational Organization: A Survey - John Roni Coyanda; Suzan Agustri (Information Technology and Science (ITScience), 2024)
Strategic planning models and the provision of information for decision making in complex strategic circumstances are research topics of great interest. This research addresses the issue of supporting strategic planning decision-making in educational foundations by building a Decision Support System (DSS) to be used by decision-makers in carrying out their strategic planning process, the DSS is integrated in the entire organisation's information system database. This research provides an overview of DSS, the college planning process, the development of DSS through the use of artificial intelligence, and a framework for planning activities at different levels of the organisation to develop strategic plans. Based on the strategic planning process model, a DSS framework is proposed, along with decision support approaches for various DSS modules. DSS provides the best support (at individual, group, and organisational levels) for all stages of strategic planning decision-making. By applying DSS, it is possible to create more perfect circumstances to achieve sustainable future-orientated institutional goals.